ADULTERY IN MOCHTAR LUBIS’ NOVEL SENJA DI JAKARTA - Raja Fauziah; Efendi Barus; M. Ali Pawiro (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The research is concerned with types of adultery based on the plot giving pictures of immoral behavior of some of the major characters committing adultery. Some of them are married, and some are not. They are brave and not ashamed of doing this immoral deed because they are not close to the doctrine of their own religion that prohibits them doing this shameful behavior. They do not even seem to be afraid of doing something which is regarded as a very sinful deed. Adultery is a sexual relationship in which a man or women has with another partner rather than his/her own spouse. Adultery is seen as a great sin in the society. Adultery maliciously interferes with marriage relations, and sometimes opens the door to divorce. (Dillon, 2016). The research is conducted using descriptive qualitative method designed to obtain information which is concerned with the current status of phenomena that occur naturally. (Ary, 1972). The results show that there are three types of adultery committed by the major characters: Visual, Mental and Physical Adulteries.